Fluoropyrimidine-induced intestinal mucosal injury is associated with the severity of chemotherapy-related diarrhea. (1st February 2019) - Ota, Kazuhiro; Takeuchi, Toshihisa; Kojima, Yuichi; Harada, Satoshi; Ozaki, Haruhiko; Sugawara, Noriaki; Hirata, Yuki; Yamaguchi, Toshifumi; Terazawa, Tetsuji; Kakimoto, Kazuki; Kii, Takayuki; Goto, Masahiro; et al.
Abstract: Background and aim: Although the fluoropyrimidines are effective chemotherapeutic agents for malignant gastrointestinal tumors, they sometimes cause enteritis with diarrhea. Severe treatment-related diarrhea may result in chemotherapy discontinuation. We investigated the relationship between diarrhea severity and fluoropyrimidine-induced small intestinal mucosal injury. Methods: We performed small bowel capsule endoscopy in patients undergoing chemotherapy including fluoropyrimidine for a malignant tumor between May 2017 and June 2018 and analyzed the relationship between the endoscopic findings and diarrhea severity. We also performed a cross-sectional analysis of patient factors and routes of chemotherapy to identify risk factors of fluoropyrimidine-induced small intestinal injury. Results: Small bowel capsule endoscopy was successfully completed in 16 eligible patients. The diarrhea grade (per the Common Terminology Criteria for Adverse Events, version 4.0) was significantly correlated with the percentage of patients with a small intestinal mucosal break (grade 0, 16.7%; grade 1, 57.1%; grade 2, 100%; p = .016, Cochran-Armitage trend test). Compared to patients receiving intravenous therapy, those receiving an orally administered fluoropyrimidine had a significantly greater number of small intestinal mucosal breaks (median number of breaks [range]; intravenous 5-fluorouracil, 0 [0–13]; oral fluoropyrimidine, 6.5 [1–20]; p = .0162, Mann–Whitney U test). Conclusions: Many patients with diarrhea caused by chemotherapy including fluoropyrimidine had small intestinal mucosal breaks. Additionally, small intestinal mucosal breaks were more severe in patients receiving a regimen of oral treatment than in those receiving a regimen of intravenous therapy. These outcomes have important implications for investigations of new strategies for preventing anti-cancer drug-induced diarrhea.